2018
DOI: 10.2147/ndt.s149403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of evening primrose oil on fatigue and quality of life in patients with multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is a chronic progressive and inflammatory disease of the central nervous system that is characterized by demyelination in the central nervous system. In regard to the prevalence of diseases and enormous costs imposed on society and the health system, finding a way to stop the progression of the disease using drugs with fewer side effects seems a serious sanitation issue to the health of the international community. This study aimed to evaluate the effect of evening primrose oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The oil of primrose has been used for the treatment of MS disease due to its immune-modulating and anti-inflammatory effects. Based on the concentration of primrose, it can show different inhibitory effects against various bacteria (Gram-positive and Gram-negative) [ 266 , 267 , 268 ]. The EO of primrose contains gamma linolenic acid (GLA).…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…The oil of primrose has been used for the treatment of MS disease due to its immune-modulating and anti-inflammatory effects. Based on the concentration of primrose, it can show different inhibitory effects against various bacteria (Gram-positive and Gram-negative) [ 266 , 267 , 268 ]. The EO of primrose contains gamma linolenic acid (GLA).…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…Saki, in a study that investigated the effect of evening primrose oil on depression, stated that although the mean score of depression and the patients' performance had been significantly reduced at the beginning of the study, weeks 4, 8, and 12 in both groups (evening primrose oil or nortriptyline therapy), in patients who received evening primrose oil, the decrease was more significant [ 35 ]. In a study, which has been conducted on patients with multiple sclerosis, it has been shown that using 1 g of evening primrose oil every 12 h for 3 months can significantly decrease pain and fatigue and also increase their life satisfaction, cognitive function and vitality [ 36 ]. SafaaHussain et al evaluated the effect of evening primrose oil in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds of Oenothera biennis are employed in the production of evening Primerose oil. This oil has shown considerable antidepressant property in a rodent model of Chronic Fatigue Syndrome 99 .…”
Section: Oenothera Biennismentioning
confidence: 99%